Legal Constructions of Body Work - Stewart, Ann (feminists@law, 2014)
This chapter explores the way in which two examples of body work - the labour involved in caring for the vulnerable elderly and in providing commercial sex - are regulated. It highlights the challenges that body work presents for labour law and exposes the wider conceptual limitations that this area of law faces in a consumer based market economy in which the boundaries between production and social reproduction are being reconstituted.